Eksplorasi Academic Hardiness pada Mahasiswa - Sutanto, Marshanda Elena; Nurcahyo, Firmanto Adi (Psychopreneur Journal, 2025)
Academic hardiness is a personality trait where people can suppress the negative effect of academic pressure and perceive academic pressure as a challenge. Academic hardiness is important to students because it can help them through college. This study aims to describe different levels of academic hardiness in various backgrounds such as students who does part time, student who works, graduate students, and difference between academic hardiness in woman and man. This study uses literature with narrative review as a design. The result of this study mainly show that students tend to have high academic hardiness. Academic hardiness is an important thing to student as it will help them to see assignments as something challenging that needs to be finished.